‘Que peut la fiction?’ Storying the Unexperienced Experience in Jorge Semprun's Fiction - Avril Tynan (Modern Humanities Research Association, 2025)
This article discusses the ethical potential of fiction as an artistic storytelling practice that facilitates the exchange of experiences by constructing a shared terrain of understanding between author and reader. Buchenwald survivor Jorge Semprun’s fiction is ethically valuable because it both facilitates the exchange of experiences and disrupts the communication of experience that lies beyond imagination. In La Montagne blanche (1986), narrative doubles defer the arrival of the experience of death so that what is exchanged is the experience as unexperienced, and the storytelling exchange itself becomes an art of survival after the Holocaust.